(untitled) (Bangladesh Pharmaceutical Journal, 2022)
Naproxen is a non-steroidal anti-inflammatory drug (NSAID) working as a non-selective cyclooxygenase (COX) inhibitor to treat inflammation, pain, fever, and various disease conditions. The current study was conducted to determine and compare several in vitro quality parameters, often commercially available 500 mg naproxen brands available in Bangladesh. According to the existing protocols, different physical parameters such as uniformity of weight, hardness, friability, disintegration time and dissolution were determined. A validated UV-visible spectrophotometric approach was used to assess the content uniformity of drug material in the collected brands. All the brands taken for this study complied with the official specifications of physical parameters. These brands contained active ingredients ranging from 91.37% up to 101.18%. On the other hand, two brands (C4 and C8) of naproxen tablets failed to meet the specification of United States Pharmacopoeia (USP), 90-110% of the labeled claim for the 500 mg naproxen tablet. These sub-standard brands possessed only 88.16% and 86.67% naproxen sodium. In conclusion, the current study indicated that eight out of the ten brands complied with quality parameters and can be used correspondingly. Bangladesh Pharmaceutical Journal 25(2): 175-179, 2022 (July)